Relationship of Exclusive Breastfeeding with History of Acute Respiratory Infection (ARI) in Children Aged 0-24 Months in Siwalima Village in November 2021 - Vica Natalia Gonga (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Acute respiratory infection (ARI) is a respiratory infection that affect both upper or lower respiratory tracts. The virus or bacteria causes ARI which lasts for 14 days. Indonesia had the highest mortality rate for ARI, in 2008 around 36.4% children infected; in 2009 around 32.1%; in 2010 around 18.2%; and in 2011 around 38.8%. The prevalence of ARI in Siwalima Health Center around 3240 children in 2020. Breastfeeding has huge benefit for both moms and babies. The prevalence of breastfeeding in Indonesia is 66.1%, but there are two provinces, West Papua (34%) and Maluku (37.2%) that have not reach the target yet. The purpose of this study is to find out if there is a relationship between Exclusive breastfeeding with history of Acute Respiratory Infection (ARI) in children in November 2021 in Siwalima Village, Aru Island, Maluku. Methods. This study uses observational analytical research methods, and cross- sectional design. The subject of this study are children age 0 - 24 months and lived in Siwalima Village. The sample of this study is using total sampling technic and there are 186 respondents. Questioners with yes or no answer are using in this study. Results. The result of chi-square test showed that there was a relationship between Exclusive breastfeeding with history of Acute Respiratory Infection (ARI) in children in November 2021 in Siwalima Village, Aru Island, Maluku. There are 84 respondent (45.2%) had ARI and 102 respondent (34.8%) didn’t, also 91 respondents (48.9%) didn’t receive exclusive breastfeeding and 95 respondent receive exclusive breastfeeding. Conclusion. Breastfeeding can be increased, especially for children aged 0 – 6 months in order to prevent infection.